ACO2 deficiency increases vulnerability to Parkinson's disease via dysregulating mitochondrial function and histone acetylation-mediated transcription of autophagy genes. - Zhu, J.; Xu, F.; Lai, H.; Yuan, H.; Li, X.Y.; Hu, J.; Li, W.; Liu, L.; Wang, C. (Communications biology, 2023)
Parkinson's disease (PD) is characterized by ?-synuclein aggregation in dopaminergic (DA) neurons, which are sensitive to oxidative stress. Mitochondria aconitase 2 (ACO2) is an essential enzyme in the tricarboxylic acid cycle that orchestrates mitochondrial and autophagic functions to energy metabolism. Though widely linked to diseases, its relation to PD has not been fully clarified. Here we revealed that the peripheral ACO2 activity was significantly decreased in PD patients and associated with their onset age and disease durations. The knock-in mouse and Drosophila models with the A252T variant displayed aggravated motor deficits and DA neuron degeneration after 6-OHDA and rotenone-induction, and the ACO2 knockdown or blockade cells showed features of mitochondrial and autophagic dysfunction. Moreover, the transcription of autophagy-related genes LC3 and Atg5 was significantly downregulated via inhibited histone acetylation at the H3K9 and H4K5 sites. These data provided multi-dimensional evidences supporting the essential roles of ACO2, and as a potential early biomarker to be used in clinical trials for assessing the effects of antioxidants in PD. Moreover, ameliorating energy metabolism by targeting ACO2 could be considered as a potential therapeutic strategy for PD and other neurodegenerative disorders.